Length–weight relationships of three Gobiidae species from the Rupsha River in southwestern Bangladesh - Hossain, Md. Yeamin; Paul, Avijit Kumar; Hossain, M.A.; Islam, M.A.; Pramanik, Md. Nasir Uddin; Islam, M.A.; Rahman, Mohammad Mustafizur (Wiley-Blackwell, 111 River St, Hoboken 07030-5774, nj USA, 2016)
This study reports the length–weight relationships (LWRs) of three Gobiidae fish species (Acentrogobius viridipunctatus, Apocryptes bato, and Odontamblyopus rubicundus) from the Rupsha River, southwestern Bangladesh. A total of 388 individuals were sampled using cast nets (mesh size ranges from 1.5 to 3.0 cm), gill nets (mesh size ranges from 2.0 to 3.0 cm) and square lift nets (mesh size ~1.5 cm) from December 2014 to November 2015. Allometric coefficient (b) values were 3.23 for A. viridipunctatus, 2.70 for A. bato, and 2.67 for O. rubicundus, respectively. The first LWRs records for these three Gobiidae species, they can be used online for FishBase as well as in future studies.